SECOND INSTAGRAM ACCOUNTS IN THE NEGOTIATION OF GENDER PERFORMATIVITY OF GEN Z MALES - Al-Mujahid, Naqil; Rozi, Fakhrur (International Journal of Cultural and Social Science, 2026)
This study examines how Generation Z males use second accounts to negotiate gender performativity on Instagram, positioning the platform as a space for interaction, image construction, self-expression, and adaptation to dominant norms of masculinity. The study employed a qualitative method with a phenomenological approach to explore participants’ experiences and meanings in using first and second accounts. Data were analysed through the interactive model of Miles, Huberman, and Saldaña, while validity was ensured through source triangulation based on interviews with 10 informants and expert triangulation. The findings show that first accounts are generally used as spaces of public representation to maintain image, fulfil standards of propriety, and present a safer self before wider audiences. Second accounts function as more intimate spaces for expressing personal, emotional, daily, and hobby-related dimensions of the self. The discussion confirms that dual-account use reflects an ongoing negotiation of masculinity in contemporary digital space today